Olive Leaf Extracts Act as Modulators of the Human Immune Response - Magrone, Thea; Spagnoletta, Anna; Salvatore, Rosaria; Magrone, Manrico; Dentamaro, Francesco; Russo, Matteo A.; Difonzo, Graziana; Summo, Carmine; Caponio, Francesco; Jirillo, Emilio (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2018)
Background: Olive tree leaves have been used in the Mediterranean area as traditional medicine in virtue of their healthy effects. Olive leaf extracts (OLEs) contain higher amounts of polyphenols than those detected in the extra virgin olive oil and fruit. Several lines of evidence support the cardioprotective, anti-oxidant and anti-inflammatory activities exerted by OLEs. Methods: Peripheral blood mononuclear cells from twenty-five healthy donors were cultured in the presence of 3 μg of two OLE extracts, extract A (resuspended in water) and extract B (resuspended in 70% ethanol). After harvesting, cell pellets were used for cytofluorimetric phenotyping, while supernatants were assayed for cytokine release by means of ELISA. Furthermore, in the same supernatants nitric oxide (NO) content was determined. Results: Both extracts, but especially extract A, increased absolute numbers of CD8+ and natural killer (NK) cells. In addition, an increased production of interferon (IFN)-γ by both extracts as an expression of T helper (h)1 activation was observed. Finally, both extracts enhanced NO release. Conclusion: OLEs, and mostly extract A, are able to in vitro modify healthy human immune response by increasing IFN-γ production which seems to be associated to the higher absolute numbers of CD8+ and NK cells and this may suggest a reinforcement of the anti-tumor activity. Furthermore, increased levels of NO may indicate the potential cardioprotective effects exerted by OLEs in virtue of their vasodilation dependent activity. Finally, OLEs are able to maintain the equilibrium between T regulatory cells and Th17 cells as evidenced by unmodified levels of interleukin (IL)-IL-10 and IL-17, respectively. In the light of these results, OLEs are potential therapeutic compounds for the treatment of chronic inflammatory disease, also preventing cardiovascular event outcome.
Keywords: nitric oxide